TRANSLATION OF GERMAN SCIENTIFIC AND TECHNICAL TERMINOLOGY: LEXICAL TRANSFORMATIONS - Ріба-Гринишин, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The peculiarities of the translation of the German scientific and technical terminology are considered in the article. The main types of lexical transformations used in the translation of the terminology under study into the Ukrainian language are described.